Serotype Distribution of Streptococcus pneumoniae causing Invasive Pneumococcal Disease at Bambino Gesù Children's Hospital in Rome: Is It Time for a New Vaccine? - Nicolosi, Luciana; Bozzola, Elena; Krzysztofiak, Andrzej; Pantosti, Annausa; Lancella, Laura; Bernaschi, Paola; Marchili, Maria Rosaria; Villani, Alberto (Journal of Pediatric Infectious Diseases, 2019)
Diseases caused by Streptococcus pneumoniae are mostly preventable infections by current immunization programs. The objective of this study was to evaluate the impact of the introduction of the heptavalent and the 13-valent pneumococcal conjugate vaccines (PCV7 and PCV13) on the burden of pneumococcal disease and on the serotype distribution of S. pneumoniae causing invasive pneumococcal diseases (IPDs) in the pediatric age over a 5-year study (from January 2008 till December 2012). We observed a decrease in IPD rate in children after PCV13 introduction despite increases in nonvaccine serotype (NVS) rates in 2011. Nevertheless, from 2012, an increase in IPD rates due to non-PCV13 serotypes was observed.
Keywords: vaccine; Streptococcus pneumoniae; invasive disease; children